Habitat partitioning, and an assessment of habitat suitability using presence data, of a large herbivore communitiy on a Zimbabwean private wildlife reserve - Traill, Lochran (Lochran William) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MFor)--University of Stellenbosch, 2003.